2004
DOI: 10.1074/jbc.m311348200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Specific Functional Subdomains within the Linker Histone H10 C-terminal Domain

Abstract: Linker histone binding to nucleosomal arrays in vitro causes linker DNA to form an apposed stem motif, stabilizes extensively folded secondary chromatin structures, and promotes self-association of individual nucleosomal arrays into oligomeric tertiary chromatin structures. To determine the involvement of the linker histone C-terminal domain (CTD) in each of these functions, and to test the hypothesis that the functions of this highly basic domain are mediated by neutralization of linker DNA negative charge, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
207
1
9

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(224 citation statements)
references
References 43 publications
7
207
1
9
Order By: Relevance
“…Point mutations and deletion experiments using histone H1.1 showed that a single cyclindependent kinase phosphorylation site at specific regions within the C-terminal domain can control the association of the entire histone molecule (33). This observation is remarkably consistent with those made using partially deleted histone H1.0 on reconstituted chromatin (34), indicating that the results from these in vitro systems can be extrapolated to the living cell.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Point mutations and deletion experiments using histone H1.1 showed that a single cyclindependent kinase phosphorylation site at specific regions within the C-terminal domain can control the association of the entire histone molecule (33). This observation is remarkably consistent with those made using partially deleted histone H1.0 on reconstituted chromatin (34), indicating that the results from these in vitro systems can be extrapolated to the living cell.…”
supporting
confidence: 71%
“…In contrast, the C terminus was required, in addition to the globular domain, for H1-dependent chromatin folding but was not sufficient for the full nuclease protection afforded the nucleosome upon H1 binding (30). Several recent studies have also revealed the prominent role that the Cterminal domain (CTD) 1 plays in determining the binding properties of histone H1s in vivo (31)(32)(33)(34) However, studies comparing the binding properties of the variants have been limited by the low sensitivity of the in vitro methods for assay-ing H1 binding. We have previously shown that fluorescence recovery after photobleaching (FRAP) has the sensitivity to detect subtle differences in binding affinities of histone H1 in live cells (33), and we have used it here to examine the role of the CTD in affecting the binding affinities of individual variants.…”
mentioning
confidence: 99%
“…MeCP2 and H1-Wild type human MeCP2 and selected RTT-causing mutations, and human H1 0 were expressed and purified as described (5,19).…”
Section: Methodsmentioning
confidence: 99%
“…32). For example, a set of studies on the role of the murine H1(0) subtype in chromatin folding in vitro suggests that this function resides in the unique amino acid composition of two subdomains within the CTD (17,18). The H1(0) CTD was also reported to bind and stimulate the activity of the apoptotic nuclease, DNA fragmentation factor DFF40/caspase-activated DNase (33).…”
Section: Discussionmentioning
confidence: 99%